Role of IgA1 protease-producing bacteria in SARS-CoV-2 infection and transmission: a hypothesis - Russell, Michael W.; Kilian, Mogens; Mestecky, Jiri (mBio, 2024)
Secretory (S) IgA antibodies against severe acute respiratory syndrome (SARS)-CoV-2 are induced in saliva and upper respiratory tract (URT) secretions by natural infection and may be critical in determining the outcome of initial infection. Secretory IgA1 (SIgA1) is the predominant isotype of antibodies in these secretions. Neutralization of SARS-CoV-2 is most effectively accomplished by polymeric antibodies such as SIgA. We hypothesize that cleavage of SIgA1 antibodies against SARS-CoV-2 by unique bacterial IgA1 proteases to univalent Fabα antibody fragments with diminished virus neutralizing activity would facilitate the descent of the virus into the lungs to cause serious disease and also enhance its airborne transmission to others. Recent studies of the nasopharyngeal microbiota of patients with SARS-CoV-2 infection have revealed significant increases in the proportions of IgA1 protease-producing bacteria in comparison with healthy subjects. Similar considerations might apply also to other respiratory viral infections including influenza, possibly explaining the original attribution of influenza to , which produces IgA1 protease.